Exotic mangrove Laguncularia racemosa litter input accelerates nutrient cycling in mangrove ecosystems - Li, Hongke; Chen, Chunlian; Zhou, Jiayi; Bai, He; Zhang, Shijie; Liu, Qiang (Frontiers in Plant Science, 2024)
Exotic plant litter presents different chemical and physical properties relative to native plant litter and alters ecosystem processes and functions that may facilitate exotic plant dispersal. However, these effects are largely unknown, especially within wetland ecosystems. This study examines whether introducing litter from the exotic mangrove Laguncularia racemosa could result in (1) accelerated community litter decomposition rates and increased nutrient cycling rates and (2) microbial community structure changes in the invaded areas. A single decomposition experiment using litterbags was conducted to examine the short-term effects of L. racemosa litter in the native mangrove forest ecosystem. The soil nutrients and microbial communities of Rhizophora stylosa, L. racemosa, and mixed forests were also compared to explore the long-term cumulative effects of L. racemosa litter in native ecosystems. The results indicated that L. racemosa has lower-quality leaf litter than R. stylosa and a significantly faster decomposition rate. This may result from changes in the soil microbial community structure caused by L. racemosa leaf litter input, which favors the decomposition of its own litter. Both the short-term and cumulative effect experiments demonstrated that L. racemosa leaf litter significantly increased the relative abundance of microbes related to litter decomposition, such as Proteobacteria and Bdellovibrionota, and enhanced the alpha diversity of soil fungi, thus creating a microbial environment conducive to L. racemosa leaf litter decomposition.Moreover, the accumulation of soil nutrients was lower under L.racemosa than under R. stylosa over several years. This may be related to the more rapid growth of L. racemosa, which causes soil nutrient absorption and storage within the plant tissues, thereby reducing the soil nutrient content.Inputting exotic mangrove L. racemosa leaf litter reduced the soil blue carbon content, potentially adversely affecting global climate change. L. racemosa may employ a unique strategy to lower soil nutrient levels in native mangroves based on its low-quality leaf litter, thereby weakening the competitive ability of native plants that are intolerant to low-nutrient conditions and enhancing its own competitive advantage to further spread into these areas. In summary, the input of exotic L. racemosa leaf litter accelerates nutrient cycling in local mangroves.